Sodium-Dependent Phosphate Transporter Protein 1 Is Involved in the Active Uptake of Inorganic Phosphate in Nephrocytes of the Kidney and the Translocation of Pi Into the Tubular Epithelial Cells in the Outer Mantle of the Giant Clam, Tridacna squamosa - Ip, Yuen K. (Frontiers Media S.A., 2022)
10.3389/fmars.2021.655714